A deletion in the STA1 promoter determines maltotriose and starch utilization in STA1+ Saccharomyces cerevisiae strains - Krogerus, Kristoffer (Appl Microbiol Biotechnol, 2019)
Diastatic strains of Saccharomyces cerevisiae are common contaminants in beer fermentations and are capable of producing an extracellular STA1-encoded glucoamylase. Recent studies have revealed variable diastatic ability in strains tested positive for STA1, and here, we elucidate genetic determinants behind this variation. We show that poorly diastatic strains have a 1162-bp deletion in the promoter of STA1. With CRISPR/Cas9-aided reverse engineering, we show that this deletion greatly decreases the ability to grow in beer and consume dextrin, and the expression of STA1. New PCR primers were designed for differentiation of highly and poorly diastatic strains based on the presence of the deletion in the STA1 promoter. In addition, using publically available whole genome sequence data, we show that the STA1 gene is prevalent among the ‘Beer 2’/‘Mosaic Beer’ brewing strains. These strains utilize maltotriose efficiently, but the mechanisms for this have been unknown. By deleting STA1 from a number of highly diastatic strains, we show here that extracellular hydrolysis of maltotriose through STA1 appears to be the dominant mechanism enabling maltotriose use during wort fermentation in STA1+ strains. The formation and retention of STA1 seems to be an alternative evolutionary strategy for efficient utilization of sugars present in brewer’s wort. The results of this study allow for the improved reliability of molecular detection methods for diastatic contaminants in beer and can be exploited for strain development where maltotriose use is desired. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s00253-019-10021-y) contains supplementary material, which is available to authorized users.